Penerapan Teknik Self Management untuk Mengurangi Penggunaan Media Sosial Pada Siswa Kelas XI SMK Nurul Islam Manyar - Amilza Afnur; Awang Setiawan Wicaksono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
There is a phenomenon that leads to behavioral symptoms of social media addiction experienced by 3 class XI students at SMK Nurul Islam Gresik. This research aims to direct students to reduce the use of social media during class. The research method used is a one group pretest-posttest experimental approach, pretest and posttest carried out based on behavioral indicators of social media addiction. Based on the results of the self-management strategy, it can reduce the use of social media in class XI students at SMK Nurul Islam Manyar.